2020
DOI: 10.3390/ijerph17238896
|View full text |Cite
|
Sign up to set email alerts
|

Study of Chemotherapy-Induced Cognitive Impairment in Women with Breast Cancer

Abstract: Background: Oncology patients experience a large number of symptoms and, those referring to cognitive performance has an ever-increasing importance in clinical practice, due to the increase in survival rates and interest in the patient’s quality of life. The studies reviewed showed that chemotherapy-related cognitive impairment might occur in 15 and 50% of oncology patients. The main objective of this research was to study the impact of chemotherapy on the cognitive function of patients with locoregional breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…The following groups of patients were excluded: patients with previous history of traumatic brain injury, neurodegenerative conditions such as Parkinson's or Alzheimer's or severe depressive symptoms, since these conditions affect cognition either directly or indirectly 29 . patients who received palliative care (due to differences in the treatment pathways and treatment regimens) 30 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following groups of patients were excluded: patients with previous history of traumatic brain injury, neurodegenerative conditions such as Parkinson's or Alzheimer's or severe depressive symptoms, since these conditions affect cognition either directly or indirectly 29 . patients who received palliative care (due to differences in the treatment pathways and treatment regimens) 30 .…”
Section: Methodsmentioning
confidence: 99%
“…patients with previous history of traumatic brain injury, neurodegenerative conditions such as Parkinson's or Alzheimer's or severe depressive symptoms, since these conditions affect cognition either directly or indirectly 29 .…”
Section: Methodsmentioning
confidence: 99%
“…Various experimental trials have demonstrated that chemotherapeutic agents, present in adjuvant therapies, may induce central nervous system toxicity negatively affecting cognitive skills reliant on the hippocampus and frontal lobes [ 24 , 25 , 26 ]. Thus, difficulties experienced by cancer patients related to the ability to pay attention, concentrate, learn, reason, process, use executive functions, and be spatially aware, are likely to be due to such neurotoxicity [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Patients frequently report cognitive changes during and after chemotherapy, with up to 50% of oncology patients experiencing deficits in cognitive function. [3,4] These cognitive impairments are commonly referred to as "chemobrain".…”
Section: Introductionmentioning
confidence: 99%